HERITAGE STATUS FOR THE HEIRS IGNORING THEIR LIABILITIES IN BALINESE LOCAL CUSTOMARY LAW PERSPECTIVE - I Nyoman Srimurti; I Ketut Widia (Kertha Wicaksana, 2018)
In human life, inheritance, especially in the form of land, is a very important asset because it is a very basic need for human beings. There are various ways to get inheritance, especially property rights on land. One of the ways in question is by being an heir. This research intends to answer the question of how the status of the estate inherited by the heirs but leaves his obligation as heir when examined from the perspective of Balinese customary law is. The type of research used in this study is empirical law study. Data analysis were done by using qualitative data analysis technique. The processed data were presented using systematic description techniques. The results of the present study indicate that the status of inheritance in any form, especially in the form of land controlled by the heir who leaves his obligation, in Balinese customary law, is illegitimate. This means that the inheritance of the heirs must be returned to those who are deemed to have the right. The technique of solving the problem of the illegality of acquisition of inheritance by the heirs who neglect their obligations, namely through non-litigation or through deliberation to reach consensus by mediation by Kerta of CustomaryVillage. If through the path of consensus can not be reached, settlement can be through litigation or legal efforts can be taken, that is by making a civil suit to the court based on the provisions of committing the act against the law.